Penerapan Tindakan Stimulasi Oral Motor pada Bayi Prematur dengan Problem Feeding untuk Meningkatkan Berat Badan di Ruang Perinatologi - Lusiana Hutapea; Veroneka Yosefpa Windahandayani; Ketut Suryani (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Background: Most premature infants experience feeding difficulties, including difficulty getting food into their mouths, limited oral capacity, and impaired tongue movement in transferring the bolus toward the posterior part of the oral cavity. This condition underscores the need for special attention in the care of premature infants, particularly in meeting their nutritional needs, which play a crucial role in supporting growth and survival. Purpose: To implement oral motor stimulation interventions for premature infants with feeding problems in the Perinatology Room of Charitas Hospitals Palembang. Method: This case study was conducted on 3 premature infants who received oral motor stimulation interventions for 3 days, with a training frequency of 2 times a day, morning and evening, for 15 minutes. Results: After oral motor stimulation interventions were performed on the three premature infants, good improvement data were obtained, namely in the strength of sucking and swallowing reflexes, and improvement in sucking movements as preparation for the transition from enteral to oral feeding. Conclusion: Providing oral motor stimulation interventions to premature infants helps improve their feeding abilities by enhancing sucking and swallowing reflexes and supporting optimal nutritional intake.